Sepuluh usulan untuk menjelaskan kebakaran di Kalimantan - Colfer, C.J.P. (Yayasan Obor Indonesia, 2003)
This short paper summarizes the conclusions of a 1999 investigation into the causes of fires in six communities in East Kalimantan. Drawing on the author’s long term experience with the Kenyah (inhabitants of five of the communities), perceived causes of the fires in these six locations were documented. Ten propositions relating to fire causes are listed here, as a preliminary step in the development of a typology of causes of fire. The first three general propositions relate to environmental conditions like drought, to human conditions like the response time required to adapt to environmental change, and to political conditions like corrupt and uncoordinated governance. Five propositions revolve around the conditions that evolve when multiple actors with different values, patterns of behaviour, and access to resources are thrown together. The final two propositions relate to economic issues (potential for gain and need). The paper concludes with a simple scoring system that may contribute to identifying fire-prone communities in the future, and to developing appropriate solutions to the relevant fire causes.